2018
DOI: 10.1021/acs.biochem.7b01108
|View full text |Cite
|
Sign up to set email alerts
|

Modulating the Molybdenum Coordination Sphere of Escherichia coli Trimethylamine N-Oxide Reductase

Abstract: The well-studied enterobacterium Escherichia coli present in the human gut can reduce trimethylamine N-oxide (TMAO) to trimethylamine during anaerobic respiration. The TMAO reductase TorA is a monomeric, bis-molybdopterin guanine dinucleotide (bis-MGD) cofactor-containing enzyme that belongs to the dimethyl sulfoxide reductase family of molybdoenzymes. We report on a system for the in vitro reconstitution of TorA with molybdenum cofactors (Moco) from different sources. Higher TMAO reductase activities for TorA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 58 publications
(136 reference statements)
2
32
0
Order By: Relevance
“…In a recent study, we reported on the direct electrocatalytic reaction of TorA and the in vitro reconstituted chimera of this enzyme in order to indicate the role of the first coordination sphere of the cofactor on its potential and its activity . TorA‐FDH was among the most active enzyme variants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In a recent study, we reported on the direct electrocatalytic reaction of TorA and the in vitro reconstituted chimera of this enzyme in order to indicate the role of the first coordination sphere of the cofactor on its potential and its activity . TorA‐FDH was among the most active enzyme variants.…”
Section: Resultsmentioning
confidence: 99%
“…The larger variation between the sensors can be explained by differences in the oxygen tolerance of the TorA‐WT. It was already reported that a contact of the WT enzyme with oxygen can damage the cofactor and as a result lower the activity of the enzyme . Since the TorA‐FDH variant seems to be less susceptible to oxidative damage compared to the WT enzyme, during the handling procedure, it was selected for the construction of the biosensor for TMAO detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other DMSO-reductase family enzymes, a sulfido ligand (Mo=S) at the metal was found. 21,22,36,[43][44][45] Accordingly, Mo=O/S distances as well as…”
Section: Mo Site Structure In Ydhv From Xasmentioning
confidence: 99%